SAE Technical Paper Series 2002
DOI: 10.4271/2002-01-2066
|View full text |Cite
|
Sign up to set email alerts
|

Operation of an Aluminum-Intensive Vehicle: Report on a Six-Year Project

Abstract: In 1994, Ford produced a small demonstration fleet of Mercury Sables with aluminum bodies. Argonne National Laboratory obtained one of these vehicles on a lease so that Laboratory staff could observe the wear characteristics of the body under normal operating conditions. The vehicle was placed in the transportation pool, parked outdoors, and used by staff members for both local and longer trips. The vehicle performed normally, except for having particularly good acceleration because of its light weight and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…engine, brakes, fuel tank, etc.) thanks to the increased efficiency achieved by the aforementioned primary lightweighting, were not considered in this analysis because of the difficulty in quantifying them, as attested by the lack of agreement in the literature (Gaines and Cuenca, 2002;Wohlecker, 2007). Instead, the same lowdisplacement internal combustion engine (ICE) was used across all scenarios (a 44 kW Volkswagen petrol engine used in the 2014 production Polo and Golf models), and the required power train adaptation to ensure constant driving performance in all scenarios was assumed to occur by means of gear ratio extension.…”
Section: Manufacturing Phasementioning
confidence: 98%
“…engine, brakes, fuel tank, etc.) thanks to the increased efficiency achieved by the aforementioned primary lightweighting, were not considered in this analysis because of the difficulty in quantifying them, as attested by the lack of agreement in the literature (Gaines and Cuenca, 2002;Wohlecker, 2007). Instead, the same lowdisplacement internal combustion engine (ICE) was used across all scenarios (a 44 kW Volkswagen petrol engine used in the 2014 production Polo and Golf models), and the required power train adaptation to ensure constant driving performance in all scenarios was assumed to occur by means of gear ratio extension.…”
Section: Manufacturing Phasementioning
confidence: 98%
“…One of the FreedomCAR goals [3] is to reduce the mass of a vehicle's by up to 50%. While other studies have discussed the impact of weight reduction on fuel economy [4,5], more research needs to be done to quantify the fuel economy sensitivity to mass reduction of advanced drivetrain configurations, vehicle platforms and drive cycles…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we have developed a detailed life cycle and materials model to quantify the GHG costs and benefits arising from lightweighting with HSS and aluminum. Distinct from previous research that has studied the maximum achievable vehicle lightweighting using aluminum and HSS (Ng et al 1999; Das et al 1997; Das 2000a, 2000b; IAI 2000; Austin et al 2002; Obenchain et al 2002; Wallentowitz et al 2006), this study has investigated material trade‐offs in the context of a specific vehicle analyzed with a detailed engineering model. Modeling a specific vehicle allows the development of a complete picture of the magnitude of GHG trade‐offs between aluminum and HSS absent the assumption of a closed‐loop aluminum infrastructure, which is decades away.…”
Section: Discussionmentioning
confidence: 99%
“…For verification purposes, we confirmed that the sum of the component material masses was approximately equal to the known mass of each material in the vehicle. Given a realistic component‐level material model of the baseline vehicle, it was possible to lightweight the vehicle, given the opportunity to substitute each major component of the vehicle with either aluminum (Tessieri and Ng 1995; Austin et al 2002; Neumann and Schindler 2002) or HSS (Das et al 1997; Das 1999). Figure 1 provides the detailed material compositions of the baseline vehicle and each LW scenario considered in this work.…”
Section: Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation